Book Pirates: Tethered Technologies and their Domestication - Klang, Mathias; Nolin, Jan (AoIR Selected Papers of Internet Research, 2013)
This work is part of a larger study on the effects of ebooks in small language markets. The results presented here are a study of more sophisticated technology users and an attempt to capture: (1) their domestication of ebook readers and surrounding technologies, and (2) their attitudes towards their tethered ebook applications. The goal is to better understand the sophisticated users as representatives of the early adopters who shape wider social technology adoption, interpretation and understanding.